Geotechnical characteristics and mitigation strategies for loess subgrades in the Ili Valley, China - Yinuo Feng; Zheng Lu; Yang Zhao; Wanxin Mo; Zhihui Ze; Yuanbiao Li (European Journal of Environmental and Civil Engineering, 2026)

Low enthalpy 3D evaporators coupled with auxiliary thermal management for rapid solar evaporation - Ze-Ming Huang; Hong-Yu Chu; Ye-Tong Liu; Xiang-Jing Mo; Jing Li; Chong-Chen Wang; Peng Wang; Xiao-Hong Yi (Chemical Engineering Journal, 2026)

Shake table tests of a full-scale stacked modular steel structure based on three-dimensional seismic isolation - Ze Mo; Ganping Shu; T.Y. Yang; Bin Wang; Binglin Lai (Engineering Structures, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Reprogramming lipid metabolism and morphology engineering in Yarrowia lipolytica for algae-free, high-titer production of esterified astaxanthin - Mo-Han Zhu; Hong-Ze Zhou; Zhijie Liu; Hong Zhu; Jun Chen; Chen Yang; Feng Liu; Qiang Hua (Chemical Engineering Journal, 2026)

Electrochemical platform for in situ metabolic profiling and therapeutic evaluation of triple-negative breast cancer - Kyeong-Mo Koo; Chang-Dae Kim; Hyung-Joo Kim; Jin-Kyu Wi; Huijung Kim; Yoon-Ze Shin; Hyuk-Jin Cha; Shin Hyuk Kang; Tae-Hyung Kim (Chemical Engineering Journal, 2026)

Vasicine derivatives as potent MAPK inhibitors for psoriasis treatment - Qing-Yan Mo; Wen-Gang Wang; Xiao-Hong Li; Yun-Hong Shen; Yun Sun; Ze-Wei Mao; Chun-Ping Wan (Molecular Diversity, 2025)

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Key role of macrophyte-dominated habitats over cyanobacteria-dominated habitats in stability of microbial sulfur cycling in freshwater lakes - Rui-Ze Li; Zhi-Jie Zhu; Xing-Hao Li; Yi-Ying Jiao; Li-Ya Zhao; Zhao-Hua Li; Mo Chen (Environmental Research, 2025)

Performance-based seismic design method of stacked modular steel building based on three-dimensional seismic isolation - Ze Mo; Binglin Lai; Ganping Shu; Peng Chen; T.Y. Yang (Engineering Structures, 2025)

The production of bronze wares of the Changsha State in the Western Han Dynasty——a case study of the Fengpengling-Taohualing Cemetery in Changsha, Hunan Province - Pingping Hu; Yanjie Wang; Guofeng Wei; Ze Mo; Chengguang Jiang; Fude Xia (Archaeological and Anthropological Sciences, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Influence of precipitation and temperature variability on anthropogenic nutrient inputs in a river watershed: Implications for environmental management - Shuhui Zhang; Xia Li; Ze Ren; Cheng Zhang; Le Fang; Xiaobiao Mo; Wei Yang; Xinhui Liu (Journal of Environmental Management, 2025)

Enhancing seismic resilience in modular steel building through three-dimensional isolation - Ze Mo; BingLin Lai; Ganping Shu; T.Y. Yang; Carlos E. Ventura; J.Y. Richard Liew (Engineering Structures, 2025)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Microplastics positively mediate soil multifunctionality in dryland - Peng-Yang Wang; Ze-Ying Zhao; Kadambot H.M. Siddique; Xiao-Bin Xiong; Hong-Yan Tao; Yue Ma; Fei Mo; Yinglong Chen; Yajie Song; William R. Burch; Baoluo Ma; Song Wang; et al. (Resources, Conservation and Recycling, 2024)

Sustainably sourced and DOPO-derived triols as hardeners for epoxy thermosets: A promising solution to synchronously improve flame retardancy, mechanical strength and toughness - Ze-Tao Xiao; Guan-Long Wu; Tian-Mo Yang; Yu Li; Yuan Hu; Manfred Döring; Xin Wang (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

The decomposition of algae has a greater impact on heavy metal transformation in freshwater lake sediments than that of macrophytes - Si-Min Xue; Shu-Qi Jiang; Rui-Ze Li; Yi-Ying Jiao; Qun Kang; Li-Ya Zhao; Zhao-hua Li; Mo Chen (Science of The Total Environment, 2024)

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Effect of dispersed species heterogeneity in carbon-based catalysts for near-infrared light-responsive synergistic antibacterial therapy - Yang Yang; Shudi Mo; Ze Zhang; Jingyu Sun; Jinghong Wen; Qilin Yu; Mingyang Liu (Chemical Engineering Journal, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Antibiotic resistance genes are closely linked with bacterial functions during anoxic-oxic treatment process of pig wastewater - Feng Huang; Chunhao Mo; Ze Cao; Yanli Pang; Yiwen Yang; Xindi Liao (Journal of Water Process Engineering, 2023)

Possible sites for a Chinese International Lunar Research Station in the Lunar South Polar Region - Teng Hu; Ze Yang; Mo Li; Carolyn H. van der Bogert; Zhizhong Kang; Xiaojian Xu; Harald Hiesinger (Planetary and Space Science, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Impacts of river discharge, coastal geomorphology, and regional sea level rise on tidal dynamics in Pearl River Estuary - Xia Li; Yanzi Cai; Zezheng Liu; Xiaobiao Mo; Li Zhang; Cheng Zhang; Baoshan Cui; Ze Ren (Frontiers in Marine Science, 2023)
Introduction Recently, accelerated sea-level rise (SLR) has raised major concerns on estuarine management and restoration because it modifies estuarine hydrodynamics, such as tidal inundation extent and amplitude, tidal current asymmetry, flood frequency, etc. Understanding underlying processes which regulate estuarine tidal dynamics is critical for mitigating potential impacts on the coastal population and development. Methods We selected the Pearl River Estuary (PRE), an estuary with a higher regional SLR compared to the global SLR as the study area. To identify the effects of regional SLR on tidal dynamics, we analyzed long-term records of four tidal variables from 19 gauge stations between 1952 and 2020, including annual highest tidal levels (AHTLs), annual lowest tidal levels (ALTLs), annual mean tidal ranges (AMTRs), and annual mean tidal levels (AMTLs). Results Results suggested that variability in tidal variables was site-specific. The AMTRs decreased gradually from offshore regions to the upper reaches of rivers with a maximum at the mouth of the estuary. In contrast, the magnitudes of the AHTLs, AMTLs, and ALTLs decreased when approaching the coastline. Distance to the coastline had the highest correlations with the AHTLs, ALTLs, and AMTLs, followed by river width and river depth. The local SLR was responsible for the temporal variability in AHTLs, ALTLs, and AMTLs at the estuarine mouth with correlation coefficients from 0.43 to 0.85 (P < 0.001) but showed low correlations with these three tidal variables at the upper reaches of rivers (P > 0.001). Instead, the tidal variables were highly correlated with river discharge at the upper reaches of rivers, especially for the AHTLs (correlation coefficient = 0.83, P < 0.0001). Conclusions Our study demonstrated that the tidal dynamics demonstrate significant spatial-temporal variability. Geomorphology, river discharge, and sea levels have jointly affected estuarine hydrodynamics.

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Bimodality and growth of the spectra of typhoon-generated waves in northern South China Sea - Dongxue Mo; Yahao Liu; Yijun Hou; Ze Liu (Acta Oceanologica Sinica, 2019)

Hurdles of CAR-T cell-based cancer immunotherapy directed against solid tumors - Bing-Lan Zhang; Di-Yuan Qin; Ze-Ming Mo; Yi Li; Wei Wei; Yong-Sheng Wang; Wei Wang; Yu-Quan Wei (Science China Life Sciences, 2016)

Outbreak of Edwardsiella tarda infection in farm-cultured giant mottled eel Anguilla marmorata in China - Ze-Quan Mo; Ling Zhou; Xiang Zhang; Lian Gan; Li Liu; Xue-Ming Dan (Fisheries Science, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)